2020
DOI: 10.1016/j.jcv.2020.104578
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the analytical sensitivity of seven commonly used commercial SARS-CoV-2 automated molecular assays

Abstract: Highlights The analytical sensitivities of seven SARS-CoV-2 molecular assays are compared. A single positive clinical specimen quantified by droplet digital PCR was used for the comparison. The Abbott, the Roche, and the Xpert Xpress assays appear more sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 32 publications
4
64
0
Order By: Relevance
“…The performance of the Molecular BD Max system for the detection of different pathogens has been evaluated previously [ 15 , 27 , 28 ]. These studies demonstrated that the BD MAX system is a good diagnostic tool with a rapid turnaround time, enabling appropriate treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the Molecular BD Max system for the detection of different pathogens has been evaluated previously [ 15 , 27 , 28 ]. These studies demonstrated that the BD MAX system is a good diagnostic tool with a rapid turnaround time, enabling appropriate treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…respiratory illness from SARS-CoV-2, especially during influenza season, because common clinical manifestations of COVID-19, including fever, cough, and dyspnoea, mimic those of other upper-respiratory infections.DiscussionTaiwan experienced two waves of imported cases of COVID-19: first from China in January to late February, and then from other countries starting in early March. As of 26 November 2020, the self-governing island reported 623 COVID-19 cases, a number that has remained relatively low due to a series of aggressive containment strategies, including mandatory social distancing and wearing masks, quarantine, and monitoring measures that have limited the local transmission of the SARS-CoV-2.The performance of the Molecular BD Max system for the detection of different pathogens has been evaluated previously[15,27,28]. These studies demonstrated that the BD MAX system is a good diagnostic tool with a rapid turnaround time, enabling appropriate treatment decisions.…”
mentioning
confidence: 99%
“…Disease surveillance largely took two forms in the dormitories: passive case detection through an onsite medical post and active case finding through close-contact investigations. Residents presenting to the medical post with symptoms of acute respiratory illness (ARI)—defined as rhinorrhoea, pharyngitis, cough, shortness of breath or fever—had a nasopharyngeal swab polymerase chain reaction (PCR) test using the Roche Cobas® 6800 assay ( Mostafa et al, 2020 ). Two local laboratories provided additional PCR capacity: the National Public Health Laboratory, using the Life Technologies TaqPath COVID-19 Combo Kit, and the Defence Science Organization using a real-time PCR assay that was developed in-house.…”
Section: Methodsmentioning
confidence: 99%
“…The kit is authorized by the Argentine Administración Nacional de Medicamentos, Alimentos y Tecnología Médica to be distributed in Argentina. The analytical sensitivity of the kit for testing the extracted RNA samples was 7.5 copies/µL (within the range of commercial RT-qPCR [100–1000 copies/mL]) [ 15 ]; clinical sensitivity and specificity were 99.03% and 99.04%, respectively, and no cross-reactivity was observed.…”
Section: Introductionmentioning
confidence: 99%